The Effect of Progressive Muscle Relaxation Exercises on the Sleep Quality of Menapause Women in the Kolaka Health Center Work Area - Naim, Rosani; Mariany, Mariany; Saputri, Ekawati; Afrianty, Iis (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Menopause is the final phase of a woman's reproduction or it is said that the last menstruation experienced by a woman has a psychological impact, especially sleep disorders.. Four of five women who were surveyed stated that their sleep was often disturbed, especially when it was difficult to fall asleep and woke up feeling it was the middle of the night so they complained of blisters in the morning because the duration of sleep at night was around 4 o'clock. The purpose of this study was to analyze the quality of sleep of mothers before and after carrying out progressive muscle relaxation exercises. Quasy Experiment Method in one group pre test-post test design is the method used with a sample of 30 respondents. The quality of sleep before exercise and after exercise progressive muscle relaxation was measured using a questionnaire. Provision of progressive muscle relaxation exercises in accordance with Standard Operating Procedures (SOP). There were significant differences in the quality of sleep of mothers before and after progressive muscle relaxation exercises on sleep quality of postmenopausal women, namely sleep quality (p value 0.000), sleep latency (p value 0.000), efficiency (p value 0.000), sleep disturbance (p value 0.000), sleep disturbance (p value 0.000), value 0.001), and disturbed activity (0.005). Postmenopausal women's sleep quality improves after doing progressive muscle relaxation exercises is effective. It can be said that the application of progressive muscle relaxation exercises in menopausal women is very good so that the quality of sleep for menopausal women is of high quality.